The Argumentation Rating Tool: Assessing and supporting teacher facilitation and student argumentation during text-based discussions - Reznitskaya, Alina; Wilkinson, Ian A.G. (Teaching and teacher education, 2021)
In this article, we describe the development and validation of the Argumentation Rating Tool (ART), an observational rating scale designed to assess the quality of teacher facilitation and student argumentation during text-based discussions in elementary language arts classrooms. We describe the theoretical and empirical foundations of the ART and report on two studies designed to establish the psychometric properties of the ART and examine its instructional value for teachers. Our findings support the reliability of the ART scores and their intended interpretation, and suggest that the ART has the potential to help teachers learn about facilitation of argumentation. •The ART was designed to assess student argumentation and teacher facilitation in text-baseddiscussions.•The ART shows evidence of reliability, validity, and instructional value for teachers.•The ART supports teachers’ learning of facilitation of argumentation.